Теоретичне обґрунтування визначення узагальнюючої якісної характеристики фінансового стану машинобудівних підприємств - Фоменко, А. В. (Видавництво Львівської політехніки, 2015)
Запропоновано теоретичний підхід до визначення узагальнювальної якісної характеристики фінансового стану машинобудівних підприємств, що дає змогу встановити адаптивну здатність до динамічних змін ендогенного та екзогенного середовища окремого підприємства, розрахувавши показники його фінансової стійкості. Обґрунтовано сукупність показників, прийнятних у сучасних умовах для визначення рівня фінансової стійкості підприємств. Given the dynamic changes in the external environment of enterprises and the low adaptability of the enterprises internal environment to them it becomes necessary that scientific economists concentrate on determining the generalizing qualitative characteristics of financial conditions of the machine-building enterprises. The content of the article meets the need to improve existing concepts of determining the financial conditions of machine-building enterprises. The key aim of the study is scientific justification of the theoretical aspects of determining the generalizing qualitative characteristics of financial conditions of machinebuilding enterprises and systematization of indicators to measure the quantitative expression of qualitative characteristics. During studying approaches to assessing the financial conditions it was found that the majority of scientists, relying on the ability of indicators to effectively respond to external challenges, focused their attention on indicators of financial stability. For determination of generalizing qualitative characteristics of financial conditions of the machine-building enterprises it is advisable to determine their financial sustainability indicators as a criterion for referring enterprises to those that are able to effectively adapt to the requirements of the environment and those who need to focus on reviewing conceptual foundations of their business activities. After indicators prioritization there were highlighted two approaches to the assessment of financial stability of machine-building enterprises, in particular, on the basis of absolute indicators and on the basis of a set of financial coefficients. Since the development of methodological supportof the enterprise financial stability assessment is meant to be used by the decision-maker directly at the enterprise, there is taken into account the importance of the criterion of minimizing the number of financial indicators due to the calculation of variation coefficients. Thus, the aticle proposes a theoretical approach to defining the generalizing qualitative characteristics of machine-building enterprises financial conditions, allowing to identify the ability of an individual enterprise to adapt to the dynamic changes of its endogenous and exogenous environment by calculating its financial stability indicators. A set of indicators for determining the level of an enterprise financial stability and being suitable for present conditions is justified.
Theoretical justification of determining the generalizing quality characteristics of machine building financial conditions
Keywords: фінансовий стан; якісна характеристика; адаптивність; машинобудівні підприємства; фінансова стійкість; динамічність середовища; внутрішні фактори; зовнішні фактори; financial situation; qualitative characteristics; adaptability; machine-building enterprises; financial stability; dynamic environment; internal factors; external factors